2013
DOI: 10.1134/s0036029513080028
|View full text |Cite
|
Sign up to set email alerts
|

Solidification dynamics under random external-temperature fluctuations

Abstract: Abstract-The nonlinear dynamic mechanisms of solid phase formation with a phase transition region are studied under periodic and random fluctuations of the cooling boundary temperature. It is theoretically shown that a mushy zone can form even at close liquid and cooling boundary temperatures due to random temperature field fluctuations. The growth of a solid phase with the mushy zone is investigated as a function of the autocovariance characteristics of random noises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have shown that in many important situations, phase transitions and non-equilibrium transport in complex systems cannot be described within the framework of traditional and classical theories. Biological, thermal, mechanical and other non-equilibrium systems can be very sensitive to external stochastic impacts; noiseinduced phase transitions very often take place in these systems [30][31][32]. Magnetic fields provoke the clusterization of ferromagnetic nanoparticles, dramatically change the physical and mechanical properties of magnetic suspensions and polymers, and induce circulating flows and hydrodynamic patterns that can intensify drug delivery in blood vessels and other biological tissues.…”
Section: The General Content Of the Issuementioning
confidence: 99%
“…Recent studies have shown that in many important situations, phase transitions and non-equilibrium transport in complex systems cannot be described within the framework of traditional and classical theories. Biological, thermal, mechanical and other non-equilibrium systems can be very sensitive to external stochastic impacts; noiseinduced phase transitions very often take place in these systems [30][31][32]. Magnetic fields provoke the clusterization of ferromagnetic nanoparticles, dramatically change the physical and mechanical properties of magnetic suspensions and polymers, and induce circulating flows and hydrodynamic patterns that can intensify drug delivery in blood vessels and other biological tissues.…”
Section: The General Content Of the Issuementioning
confidence: 99%